2001
DOI: 10.1006/juec.2000.2188
|View full text |Cite
|
Sign up to set email alerts
|

Race, Immigrant Status, and Housing Tenure Choice

Abstract: This paper applies Census microdata from 1980 and 1990 to assess the determinants of housing tenure choice among racial and ethnic groups in the Los Angeles metropolitan area. Like previous research, our results indicate that endowment differences (income, education, and immigrant status) largely explain the homeownership gap between Latinos and whites. In contrast to previous work, we find that Asians are as likely to choose homeownership as are whites, and that status as an immigrant did not portend lower ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
166
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 16 publications
(59 reference statements)
12
166
2
2
Order By: Relevance
“…Finally, executives are more likely to own than non-executives, which likely reflects the influence of income on ownership. These results are consistent with those found by Hendershott et al (2009) using Australian data and by Painter et al (2001) and Jepsen and Jepsen (2009) using U.S. data.…”
Section: Wages and Housing Costssupporting
confidence: 91%
“…Finally, executives are more likely to own than non-executives, which likely reflects the influence of income on ownership. These results are consistent with those found by Hendershott et al (2009) using Australian data and by Painter et al (2001) and Jepsen and Jepsen (2009) using U.S. data.…”
Section: Wages and Housing Costssupporting
confidence: 91%
“…Wachter and Megbolugbe (1992) and Painter, Gabriel, and Meyers (2001a) examine the influence of racial differences in income on homeownership and the transition to homeownership, respectively. Both find that endowment differences explain a substantial portion of the racial differences.…”
Section: Introduction  mentioning
confidence: 99%
“…Goudy (1977) found that social dimensions were more important in determining residential satisfaction than previously thought. Other factors have been found to alter resident perception, including race (Howarth, 2001;Painter, Gabriel, & Myers, 2001). …”
mentioning
confidence: 99%